ا لمحر ب قي ا لا حا د يث ا لنبو ية من خلا ل سنن ا بن ما خحا - Deden Taufik Hidayat (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2012)
History records that the Arabs before Islam interacted with the non-Arabs, especially through the trading process. In addition, the Kaaba frequented by the non-Arabs which has experienced partial conquest by the Greek and Latin. Jews who spoke Hebrew and Christians who spoke Syriac had lived with them for centuries. This allowed influenced Arabic by foreign languages into Arabic (ta'rib) had special adjusments with oral Arabs as a whol so it could be used bu all of them. Hence, it cannot be denied that words Arabization results (mu'arrab) are in the Qur'an and Hadith. This paper attempts to analyze mu'arrab according to the hadith in the bookm Sunan Ibn Majah which reached 67 words consisting of 22 words derived from Greek, 8 words derived from Syriac, and 6 words derived from Latin.